2013
DOI: 10.1111/dmcn.12331
|View full text |Cite
|
Sign up to set email alerts
|

An Australian population study of factors associated with MRI patterns in cerebral palsy

Abstract: ABBREVIATIONS GMIGrey RESULTS White matter injury was the most common MRI pattern (45%), followed by grey matter injury (14%), normal imaging (13%), malformations (10%), focal vascular insults (9%), and miscellaneous patterns (7%). Parity, birth gestation, level of neonatal care, Apgar score, and time to established respiration varied between MRI patterns (p<0.01). Nulliparity was most strongly associated with focal vascular insults, whereas multiparity was associated only with malformations. Grey matter injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
52
6
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 21 publications
5
52
6
2
Order By: Relevance
“…This manual was included in the Reference and Training Manual of the SCPE (www.scpenetwork.eu/en/rtm/). 2 The literature review for other classification systems of MRI findings in CP identified 49 publications, 10 of which qualified for further analysis because they used specific classification systems: two were reviews, 8,9 five population based studies, 11,[21][22][23][24] and three focused on a specific CP subtype. [25][26][27] All these studies had in common a high proportion of abnormal MRIs (83-87%).…”
Section: Resultsmentioning
confidence: 99%
“…This manual was included in the Reference and Training Manual of the SCPE (www.scpenetwork.eu/en/rtm/). 2 The literature review for other classification systems of MRI findings in CP identified 49 publications, 10 of which qualified for further analysis because they used specific classification systems: two were reviews, 8,9 five population based studies, 11,[21][22][23][24] and three focused on a specific CP subtype. [25][26][27] All these studies had in common a high proportion of abnormal MRIs (83-87%).…”
Section: Resultsmentioning
confidence: 99%
“…An insult close to term causes predominantly cortical and subcortical grey matter lesions (e.g. injuries involving the thalamus and basal ganglia) [9, 10]. The timing of the brain disturbance, in addition to its size and location, has been reported to be closely related to the severity of motor impairments [9, 11].…”
Section: Introductionmentioning
confidence: 99%
“…This was based on the earlier described assumption that the basic pattern of brain lesion in this group is WMDI. 22 The medical records also confirmed the children's history supporting this decision. A bivariate model was run in which the limit and rate were assumed to depend on both the basic pattern of brain lesion and the intervention with an interaction, i.e.…”
mentioning
confidence: 60%